Evaluation of Hazard Communication Implementation in the “X” Limited Liability Company (LLC) based on OSHA Document Standard - Aulia, Putri Mahmud Hasan Robiatul; Syamila, Ana Islamiyah; Ode, Taufan Asrisyah (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Abstract Introduction: Based on a report from the Ministry of Manpower, throughout 2021 there have been around 48,195 cases of occupational accidents and diseases in various industries. One worker factor affecting work accidents is the lack of OSH knowledge. Hazard communication is important in improving workers' expertise and safe behavior. “X” LLC is one of the high-risk industries where the application of hazard communication components, especially training at “X” LLC , is still very limited and has not fulfilled the training components in the OSHA standard. This study aims to evaluate the implementation of hazard communication at “X” LLC with the guidance of OSHA documents.[SDL1] [SDL2] Methods: This research is evaluative. The unit of analysis in this research is the hazard communication facility implemented by “X” LLC Includes information from HSE officers and workers. Observation results were compared with the implementation of hazard communication with OSHA documents.Results: Based on the results of observations made, it was found that the suitability of the implementation of hazard communication implemented by “X” LLC by OSHA documents of 65% (good) [SDL3] with a percentage of hazard classification suitability was 50% (sufficient), suitability of labeling was 71% (good), suitability of installation of signs and posters was 80% (very good), suitability of safety data sheets was 100%, suitability of socialization was 57% (good), and of implementation of training was 33% (sufficient). With these observations, it affects workers' understanding of hazards and hazard handling in their work area where workers' understanding of hazard communication comes more from experience and initial information due to limited forms of communication and training.Conclusion: Evaluation of the implementation of hazard communication at “X” LLC obtained a conformity percentage of 65% (good) with several components requiring improvement started from the arrangement of production materials according to health hazards, adding communication media and increasing the implementation of OHS training, especially training in chemical handling, risk control and first aid in work accidents.